Tinjauan Filsafat Sila Ke-4 Pancasila Terhadap Pilihan Wakil Rakyat Oleh Mahasiswa - Nazlah Aulia (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This research is entitled a “Review of the 4th principle of Pancasila philosophy on the choice of people’s representatives by students” with aims to review the philosophy of the fourth principle of Pancasila, which is democracy, towards the choice of representatives by students. The data collection methods used in this research include literature studies, interviews, and observations of students' voting behavior towards representatives. The results of this research indicate that students tend to choose representatives who are considered able to represent their voices and interests well. They also choose representatives who have integrity, competence, and good morals in accordance with the values of the fourth principle of Pancasila this research will contribute to a better understanding of how the values of Pancasila, especially the fourth principle, can influence the choice of representatives by students. Furthermore, the results of this research are expected to provide insights for leaders and aspiring leaders to better understand the hopes and needs of students in choosing representatives..